Methods And Techniques of Teaching in Mathematics Lessons in Primary School and Their Positive and Negative Aspects - Xursanova Zilola Mirzaxolmatovna; Fozilov Jakhongir Ibrokhimovich; Abduraxmonova Mohinur Furqatjon qizi (Peerian Journals Publishing, 2022)
This article discusses some methods and techniques of teaching in mathematics lessons in primary school and identifies their positive and negative aspects.
Keywords: Primary school; methods; independent work; joint work